Peluang dan Tantangan Kecerdasan Buatan Bagi Generasi Muda - Yulita Sirinti Pongtambing; Felycitae Ekalaya Appa; A. Muh. Amil Siddik; Eliyah A M Sampetoding; Harsi Admawati; Arini Anestesia Purba; Arnold Sau; Esther S Manapa (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2023)
Artificial Intelligence is the ability of computers to mimic human activities and execute tasks that normally require human intelligence. This service activity is a collaboration between young lecturers in providing understanding that is accommodated by the Strategic Studies Division of the Regional Leadership Council of the Indonesian Christian Youth Movement in South Sulawesi Province (DPD GAMKI SULSEL). The method is by way of Focus Group Discussion (FGD) with young lecturers from five universities in Indonesia. Based on the results of the FGD, the use of Artificial Intelligence for each field of science (Information Systems, Health, Education and Industry) has different roles and contributions. The use of Artificial Intelligence will benefit human resources if it is used according to the context of their knowledge. However, Artificial Intelligence can be dangerous if not used according to proper science. In using Artificial Intelligence, humans must understand their role as learners